ANALISIS PENGARUH CITRA MEREK, LABEL HALAL, DAN IKLAN TERHADAP LOYALITAS PELANGGAN PRODUK KOSMETIK HERBAL MORESKIN DI SRAGEN - Handayani, Tri; Suseno, Y. Djoko; Widajanti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
The purchase of cosmetic product is a need that must be fulfilled for some women. The existance of cosmetics that have various types, colors, and advantagel in providing function for customers requires the cosmetics industry to further develop production tecnology and develop its marketing strategies to get position on the market. The study aims to determine the effect partially between ; brand image, a halal label and advertising on customer loyalty. The population is archipelago Natural PT consumer in Keadawung sub district Sragen regency in 2019. The sample was take by puposive random samplingbof 100 respondents. Data collection tecniquel use quitionanaires, after that has been tasted using instrument namely validity and reabibility. Classic asummtion test, namely normaly, multicolonearity, heterosdastisity, and autocorrelation. Hyphotesis testing uses multiple linear regression, t test, f test of model accuraly and coeffisient of determinan.The inquiry of the brand image variable is valid, the inqury of the variable halal label is valid, the inqury of the variable advertising is valid, and the inqury of variable customer loyalty is valid also. The multicolonearity test no multicolonearity, hetereskedastisicity test no heterskedasticity, the autocorrelation test no autocorrelation, and normacility test is normacility. Research of result is: â€œbrand image, halal label and advertising there are a significant effect on customer loyalty moreskin cosmetic product in Kedawung sub district Sragen regencyâ€.